Stagnation point flow of Casson fluid over exponentially stretching sheet with variable thermal conductivity and Newtonian heating - Ahmad, Kartini; Wahid, Zaharah; Hanouf, Zahir (Institute of Research and Journals, 2017)
In this paper, we investigate the effects of variable thermal conductivity and Newtonian heating on the stagnation point flow of Casson fluid over exponentially stretching sheet. The governing partial differential equations which govern the fluid flow are reduced to ordinary differential equations by imposing suitable similarity transformation. The boundary layer equations are solved numerically using a finite-difference scheme for some embedded parameters, such as the Deborah number β, ratio of free stream velocity to stretching rate λ, fluid variable thermal conductivity ε, Prandtl number Pr and Biot number Bi. The velocity and the temperature profiles within the boundary layer region are depicted in the form of graphs.